The Role of TRPC6 in Renal Ischemia/Reperfusion and Cellular Hypoxia/Reoxygenation Injuries - Hou, Xin; Huang, Mengjun; Zeng, Xixi; Zhang, Yanhong; Sun, Anbang; Wu, Qifang; Zhu, Lin; Zhao, Hu; Liao, Yanhong (Frontiers in Molecular Biosciences, 2021)
Renal ischemia/reperfusion (I/R), a major cause of acute kidney injury (AKI), is a serious clinical event in patients during post-renal transplantation. I/R is associated with renal dysfunction, and tubular apoptosis and calcium (Ca2+) overload has been reported to be a crucial factor on tubular apoptosis in I/R injury (IRI). The canonical transient receptor potential channel 6 (TRPC6), a type of non-selective Ca2+ channels, is involved in many renal diseases. This study explored the potential beneficial impact of TRPC6 knockout (TRPC6-/-) and the relevant cellular mechanisms against I/R-induced AKI in mice. Measuring changes of renal function, apoptotic index and autophagy in mouse kidneys that suffered 24 h reperfusion after 40 min ischemia, and working in vitro with primary tubular epithelial cells (TEC) that suffered 24 h reoxygenation after 24 h hypoxia, we found that: (i) IRI tissues had increased TRPC6 expression and TRPC6 knockout significantly ameliorated renal damage induced by IRI; (ii) TRPC6 knockout enhanced the level of autophagy, alleviated the depolarization of mitochondrial membrane potential (ψm, MMP) and apoptotic changes upon IRI; and, (iii) IRI tissues had increased p-AKT and p-ERK1/2 expressions, while TRPC6 knockout could markedly reduce the phosphorylation of AKT and ERK1/2. These discoveries suggest that by reducing Ca2+ overload, the underlying protective mechanism of TRPC6-/- may be involved in down-regulation of PI3K/AKT and ERK signaling, which is likely to provide a new avenue for future AKI therapies.